Thực trạng quản lí dạy học hòa nhập cho trẻ khuyết tật tại các trường tiểu học ở khu vực Nam Trung Bộ - Võ, Kim Long (Tạp chí Giáo dục, 2024)
In recent years, the management of inclusive teaching for children with disabilities at primary schools in the South Central region has achieved certain results. However, many difficulties still exist and reveal limitations and inadequacies. This article presents some concepts and surveys the current situation of managing inclusive teaching activities for children with disabilities at primary schools in the South Central region. The results show that management of inclusive teaching for children with disabilities is rarely implemented and the implementation results are only at an average level; most school administrators do not have a plan to monitor the implementation of flexible, inclusive teaching adjustments for classrooms with children with disabilities; management of testing and assessment of inclusive teaching results for children with disabilities is rarely done and the results are only average and still contain many confusions and inadequacies; management of facilities and equipment for inclusive teaching for children with disabilities is performed at a weak level; the management of administrators and teachers participating in inclusive teaching activities for children with disabilities is rarely done and the results are not high. The above situation is an important basis to propose a number of measures to improve the effectiveness of managing inclusive teaching activities for children with disabilities at primary schools in the South Central region.